Is there Really a European Business Cycle? - Robert Inklaar; Jakob de Haan (Center for Economic Studies and ifo Institute (CESifo), 2000)
In this paper we argue that in contrast to the conclusion of Artis and Zhang, there is not much evidence in support of the view that increased exchange rate stability is related to more synchronised business cycles in Europe. This finding may have important consequences, as existing differences in business cycles in the EMU-countries may not disappear due to further monetary integration, making a common monetary policy hazardous.
Keywords: 330; Business cycles; ERM; EMU